Havasupai Habitat A. F. Whiting's Ethnography of a Traditional Indian Culture - Whiting, A. F. (University of Arizona Press, 2020)
The Havasupai Indians have lived for centuries in Cataract Canyon, and even came to be confined there by treaty. When anthopologist Alfred F. Whiting set out to study the Havasupai in the early 1940s, he found a culture that in many aspect remained unchanged. In Havasupai Habitat editors Weber and Seaman have distilled Whiting's ethnographic research. Part I comprises ten thematic chapters dealing with various aspects of culture, such as hunting and gathering, child care, housing, and religion. Part II offers a systematic presentation of Havasupai knowledge of weather and astronomy, minerals, animals, and plants; and for each item listed, Whiting has provided scientific and common English terminology, phonetic spelling, and a description of usage. Published in 1985, Havasupai Habitat offers a rich ethnography on lifeways of the Havasupai people.